Synthesis, Characterization and Properties of Heterobimetallic Complexes of Zinc(II) Dithiocarbamate Derivatives with Cobalt, Nickel and Copper metal Ions - A. Mustafa, Ihsan; M. Al-Ramadany, Omar; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
Several heterobimetallic complexes of the general formula [Zn (R-dtc)2·MCI2]n, where R-dtc is methyl-, cycloheptyl- or dicyclohexyl-dithiocarbamate, M==Co, Ni, Cu and n = 1 or 2, have been prepared from the reaction of the presursor compound Zn(R-dtc)2 (prepared from Zinc(II) salt and the sodium or potassium dithiocarbamate derivative) and the corresponding anhydrous metal salt MCl2 in non-aqueous solvents and in different molar ratios. The complexs have been characterized physicochemically and spectroscopically. Suggested structures for the complexes have been given and discussed.